2022
DOI: 10.1051/0004-6361/202141762
|View full text |Cite
|
Sign up to set email alerts
|

The MUSE Extremely Deep Field: Evidence for SFR-induced cores in dark-matter dominated galaxies atz≃ 1

Abstract: Context. Disc-halo decompositions z = 1 − 2 star-forming galaxies (SFGs) at z > 1 are often limited to massive galaxies (M⋆ > 1010 M⊙) and rely on either deep integral field spectroscopy data or stacking analyses. Aims. We present a study of the dark-matter (DM) content of nine z ≈ 1 SFGs selected among the brightest [O II] emitters in the deepest Multi-Unit Spectrograph Explorer (MUSE) field to date, namely the 140 h MUSE Extremely Deep Field. These SFGs have low stellar masses, ranging from 108.5 to 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 205 publications
(278 reference statements)
5
13
1
Order By: Relevance
“…Providing the various results and comparisons of the NFW and Burkert halo in the case of individual and coadded RCs, we found that our current sample favors the Burkert halo model and also agrees quite well with the simulations. Moreover, the recent studies by Genzel et al (2020) and Bouché et al (2022) also found a cored profile in majority of their SFGs at z ∼ 1. Therefore, we focus on discussing the Burkert halo results in what follows.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Providing the various results and comparisons of the NFW and Burkert halo in the case of individual and coadded RCs, we found that our current sample favors the Burkert halo model and also agrees quite well with the simulations. Moreover, the recent studies by Genzel et al (2020) and Bouché et al (2022) also found a cored profile in majority of their SFGs at z ∼ 1. Therefore, we focus on discussing the Burkert halo results in what follows.…”
Section: Discussionmentioning
confidence: 72%
“…In particular, Genzel et al (2020) dynamically mass modeled the RCs of 41 star-forming galaxies (SFGs), and provided the first piece of evidence of a cored DM profile at high-z (in the majority of the sample). Moreover, in a more recent study, Bouché et al (2022) dynamically mass-modeled the nine z ≈ 1 SFGs and they show that, similar to the z ∼ 1 sample of Genzel et al (2020), a significant fraction of their sample also shows evidence of a cored DM profile. The study of Bouché et al (2022) also shows that the DM "cored" feature is generally associated with galaxies with low stellar-to-halo mass, while "cusps" are found to be a function of strong star-formation activity.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…They find an anticorrelation between the inner dark matter density (measured at 150 pc) and M * /M 200 , with the approximate transition from cuspy to cored systems occurring at M * /M 200 ∼ 5 × 10 −4 , exactly as predicted by [152]. These results have been corroborated and expanded upon by [22]. Their data overlap with [21] at M * /M 200 ∼ 5×10 −3 , but extend to higher M * /M 200 , showing the increasing inefficiency of dark matter heating as M * /M 200 rises above ∼ 10 −2 , again as predicted by [152].…”
Section: The Inner Dark Matter Density Of Dwarfsmentioning
confidence: 52%
“…Indeed, there is mounting dynamical evidence for this in dwarf galaxies at both low and high redshift [e.g. 21,22,23]. Finally, for the very smallest galaxies (M * < 10 5−6 M ), ionising radiation from the first stars and galaxies in the early Universe (z ∼ 8 − 12) heats their ISM shutting off further accretion of cold gas [e.g.…”
Section: Introduction and Contextmentioning
confidence: 99%